Revisiting the efficiency and institutions debate: The interaction of legal origins and ethnic heterogeneity - Ioannis Bournakis; Dimitris Christopoulos; Marian Rizov (University of Lincoln, Lincoln International Business School, Lincoln Economics and Finance Research Group (LEAF), 2018)
We analyse the interaction between legal origins and ethnic heterogeneity and their combined impact on national efficiency. We hypothesise that in the presence of high ethnic heterogeneity common-law system performs worse than civil-law one in terms of economic efficiency. Our empirical tests on the sample of African countries support our hypothesis.
Keywords: K15; K40; O10; O43; O47; 330; national efficiency; institutions; legal origins; ethnic heterogeneity